O ensino da Matemática e a utilização das TIC nas escolas estaduais da cidade de Erechim-RS: uma investigação - Battisti, Sabrina (2017)
The present research has as its object of study the use of ICT in Mathematics teaching. The primary objectives are to investigate the reality of the state schools of the city of Erechim/RS regarding the use of ICT to teach mathematics in the final years of Elementary School and; to present a pedagogical proposal of virtual activities for the teaching of Mathematics. A reflection on the initial and continuous formation of teachers is presented, alongside with public policies that stimulate the presence of ICT in the educational environment and the importance of its use for the process of Mathematics teaching and learning. The methodology uses a quali-quanti study that has by its instrument of data collection a form application to Mathematics teachers that compose the sample of the study. The results show that it is necessary to invest more in continuing education courses based on the insertion of ICT in pedagogical practice, since schools have an adequate infrastructure in terms of technological resources, but teachers do not feel able to use them during math classes. The research grant contemplates a pedagogical proposal with virtual activities to teach Mathematics developed from the exploration of mathematical software and educational sites, to be made available to the mathematics teachers of the schools involved.